2022
DOI: 10.3389/fphys.2022.987835
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prognostic biomarker of lung cancer patients with brain metastases: Recurrence quantification analysis of heart rate variability

Abstract: Background: It has previously been shown that the time-domain characteristic of heart rate variability (HRV) is an independent prognostic factor for lung cancer patients with brain metastasis (LCBM). However, it is unclear whether the nonlinear dynamic features contained in HRV are associated with prognosis in patients with LCBM. Recurrence quantification analysis (RQA) is a common nonlinear method used to characterize the complexity of heartbeat interval time series. This study was aimed to explore the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“… Mohebbi and Ghassemian (2011) showed that compared with the ECG signals that are distant from paroxysmal atrial fibrillation, RQA indexes, such as Lmean, Lmax, REC, and ShanEn with the ECG signals that are before paroxysmal atrial fibrillation were significantly higher. Li et al (2022) showed that higher Lmax is significantly associated with shorter overall survival in LC patients with brain metastasis. Similar to the above studies, our results showed that the RQA indexes REC and DET are independent prognostic factors for the overall survival of advanced NSCLC patients ( p < 0.05), indicating that the increase in REC and DET, that is, the decrease in heartbeat complexity, is an independent risk factor for poor prognosis in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“… Mohebbi and Ghassemian (2011) showed that compared with the ECG signals that are distant from paroxysmal atrial fibrillation, RQA indexes, such as Lmean, Lmax, REC, and ShanEn with the ECG signals that are before paroxysmal atrial fibrillation were significantly higher. Li et al (2022) showed that higher Lmax is significantly associated with shorter overall survival in LC patients with brain metastasis. Similar to the above studies, our results showed that the RQA indexes REC and DET are independent prognostic factors for the overall survival of advanced NSCLC patients ( p < 0.05), indicating that the increase in REC and DET, that is, the decrease in heartbeat complexity, is an independent risk factor for poor prognosis in patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…Because the RQA can be applied to short, nonstationary and high-noise signal sequences of the R-R interval, where there is not a strict requirement for the length of data, it has been used in many studies on heart rate dynamics ( Mohebbi and Ghassemian, 2011 ; Acharya et al, 2014 ; Li et al, 2022 ). For example, Acharya et al (2014) showed that Lmean, Lmax, REC, and DET in patients with coronary artery disease are significantly higher than those in healthy populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations